Effectiveness of Qanun Jinayat Implementation in Addressing Online Gambling Crimes in Aceh Province - Sari Yulis; Herlin Herlin; Muksalmina Muksalmina; Friska Anggi Siregar; Yuni Zahratul Muna (FASYA Press, 2026)
Online gambling in Aceh represents a borderless and technology-driven transformation of maisir that challenges the practical application of Qanun Aceh No. 6 of 2014 on Jinayat Law. Rather than indicating a complete legal vacuum, the problem lies in interpretive and enforcement challenges arising from digital gambling modalities, electronic evidence, and inter-agency coordination. This paper aims to analyze the effectiveness of Qanun Jinayat implementation in addressing online gambling crimes, assess enforcement practices among relevant institutions, and formulate policy recommendations that align syariah-based legality with contemporary digital realities. Employing a qualitative juridical-sociological approach, this study combines semi-structured interviews with law-enforcement and syariah institutions and document analysis of regulations, case data, and court decisions. The data were examined through thematic analysis and triangulated to ensure validity. The findings indicate that the doctrinal elements of maisir under Qanun Jinayat are sufficiently broad to cover gambling activities, including online forms. However, interpretive difficulties arise when betting activities involve tokens, e-wallet balances, virtual accounts, or in game mechanisms. Electronic evidence, such as screenshots, bank transfer records, digital logs, and online communication traces, is increasingly used in practice, provided that authenticity, relevance, and chain of custody standards are fulfilled. Enforcement agencies rely on undercover techniques, financial tracing, and basic digital forensics, yet investigations remain constrained by encryption, cross-border servers, limited forensic infrastructure, and uneven regional capacity. Preventive efforts by municipal enforcement authorities, syariah institutions, prosecutors, and community actors show potential but remain inconsistent due to budget limitations and digital-literacy gaps. Courts also consider non-juridical factors, including repentance, motive, and socio-economic background, while maintaining due-process guarantees. The study concludes that Aceh has developed an emerging integrated criminal justice response combining repressive, preventive, and educational measures. Nevertheless, its effectiveness requires clearer interpretive guidelines, formal inter-agency protocols, certified regional digital forensic facilities, standardized procedures for electronic evidence, sustained capacity-building, and community-based digital literacy programs.